Analisis Pengaruh Faktor Penggunaan Baju Baru (Fast fashion) ke Pengguna Baju Bekas (Thrifting) Menggunakan Metode K-Means Clustering (Studi Kasus: Toko Thriftboys.id) - Raffi Dima Sampurno; Agung Triayudi; Ratih Titi Komala Sari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The emergence of a habit in Indonesia and even the world, namely the use of used clothes (thrifting) became the idea for this research. This new habit is known to be able to reduce the production of textile waste in the world. The purpose of this study was to obtain analysis results that affect the use of new clothes (fast fashion) on the use of used clothes (thrifting). Using the K-means Clustering method and using several parameters, including age, quality, price, and sustainability or awareness. The method of collecting data is through a questionnaire and the research material is the buyers found in the online store Instagram (thriftboys.id). From the results of the clustering process that researchers have done using the K-means algorithm with manual calculations and rapidminer applications, the conclusions consist of; 1) In clusters 1 and 2 the age factor shifting from fast fashion to thhirft is 23 years, while in cluster 3 it is 25 years, 2) In the three clusters the average income that shifts from fast fashion to thhirf is group 3 or the range of 200000 -500000, 3) In the third cluster, people switch from fast fashion to thrift because of the good quality of goods, and 4) In clusters 2 and 3 more people are aware of textile waste for the world. Meanwhile, cluster 1 has the same number of conscious and unconscious waste.